PEMOTIVASIAN GURU DAN SUPERVISI KEPALA SEKOLAH SEBAGAI UPAYA MENINGKATKAN KINERJA GURU DI SMK NEGERI RAJAPOLAH - SRI NURHAYATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Evidence that the performance of teachers at SMK Negeri Rajapolah is not yet professional, in carrying out their main duties and functions, is teaching planning that is not in accordance with the demands, teaching that is not in accordance with planning, evaluating student learning outcomes with the right technique and it is proven that the students have not been able to learn properly. good or meaningful. Teacher performance has not been optimal, especially in terms of discipline and compliance with regulations. The research formula is "Is the provision of motivation or motivation of teachers and supervision of principals can improve teacher performance?". The purpose of the study was to find out how to find the best way to motivate and supervise school principals in improving teacher performance at SMK Negeri Rajapolah Tasikmalaya. The research method used is Action Research, with data collection by interview, observation, and collection of related documents. The conclusion in this School Action Research is that the provision of motivation or the provision of motivation and supervision of the principal can improve teacher performance. In the first cycle, a total of 78 teachers or about 74.3% can perform their performance and teachers are motivated to come in every activity carried out. A total of 78 teachers (74.3%) were present 10 minutes before the start of learning while the remaining 27 teachers or about 25.7% were still less motivated, lacked time discipline, arrived late and were not punctual in carrying out teaching and learning activities. in the classroom. Furthermore, the results of observations showed that 53 teachers or about 50% of teachers did not yet have learning administration tools for learning preparation, and the students or 5% already had learning preparations or lesson plans. In the second cycle as many as 105 teachers or 100% have increased in terms of attendance in each activity. Based on the results of observations as many as 78 teachers or about 74.3% have tried and made learning preparation administration tools or lesson plans. In cycle II, it shows that teacher motivation has experienced a significant increase of 100%, teachers are no longer late to school, on average the teachers come 10 minutes before the implementation of learning. In terms of preparing learning tools or lesson plans, 79 people (75%) were able to make and implement lessons according to the plan. Referring to the data obtained in Cycle II, it showed significant results, when the teachers came to class, they were good, in conducting learning preparation tools they were good. So that the provision of motivation and the implementation of the supervision of the principal can actually improve the performance of teachers as professional teachers. Teachers are aware of the importance of improving teacher performance in accordance with their main duties and responsibilities. The provision of motivation and implementation of supervision to teachers carried out by the principal has an impact on the increasing performance of teachers at SMK Negeri Rajapolah Tasikmalaya.